Development of the Traditional Tape Ketan Into Probiotic Drink - Endang S. Rahayu; Asri Nursiwi; Bedri Sekar N; Supriyanto Supriyanto (Indonesian Association of Food Technologists, 2018)
Probiotics are living microorganism which give health benefit when consumed. Probiotic needs a ‘vehicle’ for their specialized actions in gastrointestinal tract. In this research, tape ketan was used as ‘vehicle’. The objective of this research was to produce probiotic tape ketan powder as an ingredient of functional beverage. Tape ketan used in this research was made by fermentation of glutinous rice with ragi and supplemented with Lactobacillus plantarum Dad 13 (107CFU/g glutinous rice). Probiotic powder was obtained using spray dryer with inlet temperature of 90oC with the addition of 35% maltodextrin. The powder was reconstituted into water with addition of pectin and sucrose. The results showed that viability of lactic acid bacteria and L. plantarum decreased after drying (0.82 and 0.90 log cycle respectively) with viable count from 1.29x1010 CFU to 1.96x109 CFU for lactic acid bacteria and from 1.04x1010 CFU to 1.32x109 CFU for L. plantarum. To obtain probiotic tape ketan beverage, 20% tape ketan powder (w/v), 0.5% pectin (w/v) and 4% sucrose (w/v) were reconstituted. Tape ketan powder which was supplemented with probiotic Lactobacillus plantarum Dad 13 is potential as an ingredient of functional beverage (from the viability after drying).